Explicație pas cu pas:
a)
[tex] \frac{x - 3}{6} + \frac{y - 2}{2} = 1 \\ \frac{ x - 3}{ \sqrt{3} } = \sqrt{3} \\ \\ x - 3y = 12 \\ x =- 3y +15 \\ -6y +15=3 = > y = 2\\x=-6+15=>x=9[/tex]
[tex](x;y) = (9;2)[/tex]
b)
[tex] {(x -y )}^{2} = (\frac{2x + 5y}{7} - \frac{{(x + y)}^{2} }{11}) \div \frac{ \sqrt{z} }{13} [/tex]
[tex](9-2)²= ( \frac{2×9+5×2}{7} - \frac{(9+2)²}{11} ) \div \frac{ \sqrt{z} }{13} \\ 49 = ( \frac{18+10}{7} - \frac{11²}{11} ) ×\frac{ 13 }{\sqrt{z}}\\49 = (4 - 11) ×\frac{ 13 }{\sqrt{z}}\\\sqrt{z}=-\frac{13}{7}[/tex]
nu există soluții reale